TINDAK TUTUR MENGKRITIK DALAM SERIAL BAHASA ARAB CRASHING EID /JĀYIBATU AL-‘ĪDI/ - Nurhannah, Childa; Triwinarti, Wiwin (UI Scholars Hub, 2025)
The speech act of criticizing is a statement that contains assessment, expression, and emotion towards the behavior and words of the speech partner or the object of criticism. The data corpus studied in this research is the speech act of criticizing in the Arabic series from Saudi Arabia جايبة العيد or Crashing Eid which aired on Netflix in 2023. This descriptive qualitative research data is processed with free listening and note-taking techniques. This study aims to analyze the form of criticizing speech acts in the Hijazi dialect of Arabic contained in the series and classify criticizing speech acts with direct and indirect categories based on Nguyen's theory (2005). The results show that the strategy that is more widely used in the data corpus is direct criticism speech, which acts as an expression of disagreement.